2017
DOI: 10.22312/sdusbed.311497
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinde Akıllı Telefon ve İnternet Bağımlılığı ile Üst Ekstremite Fonksiyonel Aktivite Düzeyleri Arasındaki İlişkinin İncelenmesi

Abstract: Bu araştırma hemşirelik öğrencilerinde akıllı telefon ve internet bağımlılığı ile üst ekstremite fonksiyonel aktivite düzeyleri arasındaki ilişkinin incelenmesi amacıyla yapıldı. Materyal-Method: Tanımlayıcı ve kesitsel desende yürütülen araştırma, Türkiye'nin batı bölgesinde yer alan bir devlet üniversitesinin 2015-2016 öğretim yılında hemşirelik bölümünde öğrenim gören, araştırmanın yapıldığı dönemde ulaşılabilen ve araştırmaya katılmayı kabul eden 289 öğrenci ile gerçekleştirildi. Araştırma verilerinin topl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
7
0
5
Order By: Relevance
“…Similar studies have also shown that gender did not affect SA. 4,7,41 On the other hand, previous studies reported that there was a difference between the genders in terms of SA. In some studies, the rate of addiction was reported to be higher in females, 9,16,42 while other studies reported that the rate of addiction was higher in males than females.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Similar studies have also shown that gender did not affect SA. 4,7,41 On the other hand, previous studies reported that there was a difference between the genders in terms of SA. In some studies, the rate of addiction was reported to be higher in females, 9,16,42 while other studies reported that the rate of addiction was higher in males than females.…”
Section: Discussionmentioning
confidence: 88%
“…11,12,38 In this study, the mean SAS-SF score of the the findings in our study, there are studies in the literature reporting that the level of SA is lower in NSs. 4,9,38,39 It is thought that this difference is due to the use of different scales to measure SA and to the sample size or individual characteristics in the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hastalığın ilk tanı anı, yaşam sonu dönem ve yas dönemi olarak üçe ayrılan palyatif bakım sürecinde hasta ve bakım veren aile üyesi arasındaki ilişki, ilk tanı öncesi ilişkilerine nazaran farklılaşabilmektedir(Yılmaz ve Sarı, 2017). Bakım süreci, birçok zorluğu beraberinde getiren ve bakım veren aile üyelerini çeşitli yönlerden etkileyen zorlu bir süreçtir.…”
unclassified